Rukun Bersama Toleransi Antar Mahasiswa Pendatang dan Mahasiswa Lokal Tanpa Menghilangkan Nilai-Nilai Adat Budaya Aceh di IAIN LANGSA - Mukaramah, Mawaddah (Mulya Literasi Publishing, 2022)
Tolerance is an attitude of respect, respect and acceptance of differences that occur among students and society. This research aims to find out the realization of social relations between immigrant students and local students at IAIN LANGSA without eliminating the indigenous cultural values of acehnese people. The subject of this study involved FTIK students consisting of immigrant and local students. The method used is a descriptive qualitative method. Data collection techniques are carried out by means of interviews, documentation and observations in research activities. Data collection tools in the form of observation guides, interview guides, and tools for documenting. The results of this study showed that there was tolerance between immigrant students and local students which was characterized by harmony between students in making consensus, and the position of immigrant students in HMJ FTIK. Tolerance in the context of association builds harmonious relationships influences both in the indigenous values of Acehnese culture